Studi Empiris Government Effectiveness Dan Trade Openness Terhadap Perdagangan Internasional - Risa Sari Pertiwi; Sri Herianingrum; Muhammad Ubaidillah Al Mustofa; Mumuh Muhammad (Jurnal Ekonomi, 2019)
This study aims to examine the impact of macroeconomic factors such as Inflation, Exchange Rates, Total Labor Force, Technology, Worldwide Government and Trade Openness on International Trade in 10 Islamic countries as the main actors of international trade Intra-OKI from 2005 to 2018. Quantitative research This applies the Panel Data Regression method to the Fixed Effect Model. Research analysis techniques use the EViews 10. software program. Empirical results show that inflation and total labour force, government effectiveness and trade openness have a significant positive effect on Intra-OKI international trade. This means that the better the quality of worldwide government and trade openness in a country will increase the country's international trade activities. In addition, exchange rates and technology do not have a significant effect on Intra-OKI international trade.